Molecular Analysis of Two Endemic Squalius Species: Evidence for Intergeneric Introgression among Cyprinids and Conservation Issues - Damir Valić; Matej Kristan Mirković; Višnja Besendorfer; Emin Teskeredžić (Fishes, 2023)
Conservation of indigenous species, especially endemic ones, is of the utmost importance. Morphological determination of species is usually not sufficient; therefore, molecular phylogenetic analyses of the Illyrian chub, Squalius illyricus, and the Zrmanja chub, Squalius zrmanjae, from the Krka River were performed. For the genetic characterization of the mitochondrial gene cytochrome b and the non-coding nuclear region Cyfun P, 15 specimens from each species were subjected to analysis. The obtained sequences were aligned with similar ones from GenBank to determine the taxonomic and phylogenetic position of these species. The obtained molecular results imply that S. zrmanjae from the Krka River has a nuclear region that resembles Dalmatian rudd, Scardinius dergle. This result implies an introgression event and the transfer of genetic information between the two genera. The investigated species are on the IUCN Red List of Threatened Species, their biological data are scarce, and further investigation and protection are needed.